(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The persistent challenge of weak business performance among micro enterprises in Nigeria highlighted the need to examine how entrepreneurial networking affected enterprise performance, particularly in Osun State. Despite increasing participation in informal and formal business activities, limited integrated evidence existed on how different forms of entrepreneurial networking jointly affected the performance of micro enterprises, thereby necessitating this study. The study therefore examined the effect of entrepreneurial networking on the performance of micro enterprises in Osun State, Nigeria, with specific objectives focusing on personal networking, social networking, operational networking, and strategic networking. A quantitative research design was adopted. Data were collected through a structured questionnaire administered to 490 respondents selected from a population of 1,370,908 micro enterprise owners using multistage sampling technique. Data were analysed using descriptive statistics involving frequency and percentage, alongside inferential statistics involving multiple regression analysis. The findings indicated an overall entrepreneurial networking contribution of 74.6%, while personal networking (B = 0.619), social networking (B = 0.755), operational networking (B = 0.829), and strategic networking (B = 0.884) all exerted significant positive effect on micro performance. The study concluded that entrepreneurial networking significantly affected the performance of micro enterprises. It was recommended that micro enterprise owners should strengthen networking activities through improved relationship building and strategic collaboration. It was also recommended that policymakers should develop supportive frameworks that encourage networking platforms and strengthen enterprise linkages for improved sustainability and growth.